Research Avenues Towards Net-Zero Cloud Platforms - Berger, Daniel S.; Kazhamiaka, Fiodar; Choukse, Esha; Goiri, Íñigo; Irvene, Celine; Misra, Pulkit; Kumbhare, Alok; Fonseca, Rodrigo; Bianchini, Ricardo (NetZero 2023: 1st Workshop on NetZero Carbon Computing, 2023)
The carbon impact of cloud providers spans on-site generators and staff emissions (scope 1), purchased energy (scope 2), and carbon embedded in chips, PCBs, racks/server enclosures, and buildings (scope 3). Scope 1 contributes negligible amounts. Before shifting to renewable energy (avenue 2 below), scope 2 made up the majority of carbon emissions. With renewable energy, scope 3 dominates carbon emissions and cloud providers pursue reducing and then offsetting the remaining emissions. With the high cost of carbon offsets, reducing carbon emissions will become a long-standing priority. This abstract describes six high-impact reseach avenues that can reduce the carbon emissions of cloud platforms by an order of magnitude. While based on internal life cycle assessments, they describe only a subset of active initiatives at Microsoft. Our carbon impact estimates are subject to confidentiality agreements with third parties to evaluate scope 3 impacts and they may change as life cycle assessments become increasingly detailed. Consequently, we focus on a qualitative description of sustainability avenues